Analisis Proksimat dan Daya Terima Sosis Analog Berbahan Dasar Tepung Ubi Banggai dan Tepung Biji Kelor - Desi Natalia Rotinsulu; Nurdiana Nurdiana; Ni Ketut Kariani (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2026)
Consumption of meat sausages has the potential to increase the risk of non-communicable diseases due to their high saturated fat content. The development of plant-based analog sausages can be a healthier alternative. Banggai sweet potato has potential as a local carbohydrate source, while moringa seeds contain relatively high protein. This study aimed to determine the acceptability and proximate composition of analog sausages made from Banggai sweet potato flour and moringa seed flour. This study was an experimental research using a Completely Randomized Design (CRD) with three formulations (F1, F2, and F3). Organoleptic testing was conducted on 30 semi-trained panelists using a 5-point hedonic scale including color, aroma, taste, and texture. Data were analyzed using Shapiro–Wilk, Kruskal–Wallis, and Mann–Whitney tests. Proximate analysis was performed on the selected formulation. The results showed significant differences in all acceptability parameters (p < 0.05). Formulation F3 was the best formulation based on panelists’ preference level. Proximate analysis of formulation F3 per 100 grams showed moisture content of 7.54%, ash content of 1.61%, protein 7.67%, fat 11.28%, and carbohydrate 21.02%. Formulation F3 had the highest acceptance level and nutritional content with potential as a plant-based protein food alternative. Further studies are needed including mineral analysis, shelf-life testing, microbiological analysis, and industrial-scale development to improve product quality.